2021
DOI: 10.1136/bjophthalmol-2021-319568
|View full text |Cite
|
Sign up to set email alerts
|

Progression of myopia in teenagers and adults: a nationwide longitudinal study of a prevalent cohort

Abstract: BackgroundThe prevalence of myopia is increasing worldwide. The purpose of this study was to evaluate the progression of myopia in teenagers and adults in France.MethodsThis nationwide prospective study followed 630 487 myopic adults and teenagers (mean age 43.4 years±18.2, 59.8% of women) between January 2013 and January 2019. Myopia and high myopia were defined as a spherical equivalent less than or equal to –0.50 and –6.00 diopters (D), respectively. Demographic data were collected at first visit and refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
0
19
2
Order By: Relevance
“…This study is the first study to observe the myopia progression rate over 2.5 years after the discontinuation of myopia control. Our results revealed that the mean myopia progression and axial elongation were about 0.22D/year and 0.12 mm/year after stopping DIMS lens wear (combining Group 2 and Group 4), and such amount of myopia progression was clinically insignificant compared with children in the same age range 25 27 .…”
Section: Discussionmentioning
confidence: 63%
“…This study is the first study to observe the myopia progression rate over 2.5 years after the discontinuation of myopia control. Our results revealed that the mean myopia progression and axial elongation were about 0.22D/year and 0.12 mm/year after stopping DIMS lens wear (combining Group 2 and Group 4), and such amount of myopia progression was clinically insignificant compared with children in the same age range 25 27 .…”
Section: Discussionmentioning
confidence: 63%
“…18 While success has been observed with MC interventions in children using a range of optical devices, myopia progression can continue into the teenage and adult years. 21,22 Hence, it is important to understand how teenagers and young adults tolerate and accept MC devices. Subjective visual quality may be impacted by factors other than simple refractive error, for example, loss of contrast, ghosting, haloes and vision stability, which are inherent artefacts of the complex optical corrective devices that are currently being used for MC.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that non‐compliance in children is associated with poorer subjective vision quality and visual clarity 18 . While success has been observed with MC interventions in children using a range of optical devices, myopia progression can continue into the teenage and adult years 21,22 . Hence, it is important to understand how teenagers and young adults tolerate and accept MC devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations